Rapid implementation of remote digital primary care in Stockholm and implications for further system-wide implementation: practitioner's and manager's experience of the Always Open mobile application - Karin Solberg Carlsson; John Øvretveit; Mikael Ohrling (Taylor & Francis Group, 2023)
AbstractObjective To contribute actionable knowledge how to increase appropriate use of digital technologies in primary care by understanding clinical managers experiences with a digital connection system, Always Open, during the COVID-19 pandemic.Design and subjects The overall design was a qualitative study with directed content analysis method. Data were collected from documents and focus group (n = 12) interviews with clinical managers (n = 99) of primary care. The seven domains of the Non-adoption, Abandonment, and challenges to the Scale-up, Spread and Sustainability (NASSS) framework was used to understand the implementation process, as described by the clinical managers.Results Focus group participants reported that their units made their own local decisions to make more use of the technology provided by the health system. Most participants considered that the technology was ready to use, despite some limitations, that included individual clinician's and patient preferences, and how ready their unit was for making changes to practice and organization. Some raised concerns about how standardizing some aspects possibly conflicted with the decentralized management model of the organization. The overall experience was reported to be positive, with an intention to sustain the achievements.Conclusion Focus group interviews found that clinical unit managers reported that they and their staff were positive about the digital technology system for remote care. For the future, they wanted changes to be made at different levels of the health system to better combine digital and physical care. Possibilities to use digital technology to integrate primary and hospital health care were identified.